DIDACTIC SIMULATION OF A SELF-STABILIZING SYSTEM: A PEDAGOGICAL APPROACH TO TEACHING EMBEDDED SYSTEMS - Louro, Antonio Henrique Figueira (Seven Editora, 2026)
This work presents a proposal for a didactic simulation of a two-dimensional self-stabilizing system, inspired by the conceptual operation of a 2D gimbal, developed on the Raspberry Pi Pico W platform. The main motivation is to provide an accessible pedagogical resource for teaching embedded systems, prioritizing the conceptual understanding of execution flow, data acquisition, processing, and feedback, without the inherent complexity of real mechanical systems. The simulation employs controlled inputs and visual and auditory outputs to represent the dynamic behavior of the system, allowing students to immediately observe the relationship between stimuli and responses. The proposal is intended for technical and undergraduate courses, as well as teacher education, standing out as an intermediate stage between theoretical study and more advanced physical projects. DOI: https://doi.org/10.56238/sevened2026.008-078